DNA barcoding of five benthic invertebrate taxa from the Mackellar Cove of the Antarctic Peninsula - Merino Valencia, Norma Mároli (2020)
The Antarctic ecosystem presents benthic organisms with unique spatial and demographic distribution and exceptional adaptations to extreme conditions; however, the genetic diversity it hosts is little known. In order to characterize the molecular diversity of 25 benthic invertebrates collected in the Mackellar Cove during the Peruvian expedition ANTAR XXIV-2017, we analyzed nucleotide sequences obtained from the mitochondrial genes COI, ARNr 16S, and nuclear ARNr 18S and 28S (for molluscs). A morphological description of the 5 taxa between molluscs, bryozoans, polychaetes and crustaceans was made. The nucleotide sequences were recorded in open access databases (BOLD and GenBank) as Margarella antarctica (A1-A5), Nacella concinna (A11-A15), Nematoflustra flagellata (A16-A20), Amphitrite kerguelensis (A21-A25) and Euphausia superba (A26-A30).